Women thriving in academia - Mahat, Marian (Surviving and thriving in academia, 2021)
In a male-dominated higher education sector characterised by overt and subtle adversities for women, the path for women in academia is rarely a simple and easy one. This book sets out to empower women in academia to unite in sharing their stories, inspiring and encouraging one another. Providing international perspectives from Asia, Australia, South Africa and the United Kingdom, and packed with real examples, success stories and practical advice from academic women at all levels, this timely text equips readers to understand how we can move higher education institutions beyond the constraints that have held highly competent women back for far too long. Chronicling both the challenges and opportunities posed by the higher education sector, and cutting across the fields of leadership, management and gender studies, the contributors offer a finely curated collection which empowers women not only to better navigate the academic world, but thrive in it.